Kinetics of biological nitrogen removal in a single sludge activated sludge process - Sehayek, Ephraim (Department of Civil Engineering, 2016)
The objective of this investigation was to develop experimental set-ups and operational procedures for accurate and reliable evaluation of the kinetic constants and sewage characteristics that influence nitrification and denitrification in the single sludge nitrification-denitrification activated sludge process.